MEKANISME VITAMIN C MENURUNKAN STRES OKSIDATIF SETELAH AKTIVITAS FISIK - Wibawa, Junian Cahyanto; Wati, Lilik Hera; Arifin, Muhammad Zainul (Journal of Sport Science and Education, 2020)
Vitamin C is a water-soluble substance  and it acts as chain-breaking antioxidant. It scavenges free radicals and reactive oxygen species (ROS), which are produced during metabolic process. Exercise can produce an imbalance between ROS and antioxidants, which leads to tissue damage related to oxidative stress. Vitamin C also acts as a supporting factor in several enzymatic reactions in the body and can increase components of the immune system. Because of the pivotal role of vitamin C in reducing free radical levels, this review article presents a characteristics and functions of vitamin c as an antioxidant to lessen the levels of free radicals which focused in exercise condition. Keywords: vitamin C; antioxidants; oxidative stress; exercise